Efficiency in the treatment of three livestock manures through a composting process with mechanized turning - Strapazzon, Ari João; Theves, Fernanda Aline Blatt; Wiesel, Patrik Gustavo; Lobo, Eduardo Alcayaga (Journal of Agriculture and Natural Resources, 2021)
This research aimed to evaluate the efficiency of the treatment of manure from three livestock production units (cattle, swine, and poultry), through composting with mechanized turning and incorporation of natural substrate (wood sawdust) in rural properties in the municipalities of Farroupilha, Relvado, and Caxias do Sul, State of Rio Grande do Sul, Brazil. The experimental design consisted of nine treatments, three for each type of manure. These were classified as: T1 (cattle manure plus wood sawdust), T2 (swine manure plus wood sawdust), and T3 (poultry manure plus wood sawdust). The process involved the daily turning of the windrows by a mechanized process and sampling was carried out in triplicate at 60, 120, and 180 days of composting, between the months of July 2018 and July 2019. After each sampling, samples were properly stored and sent to the Chemistry Laboratory of the University of Santa Cruz do Sul for analysis of the following variables: Calcium (Ca), Cation Exchange Capacity (CTC), Phosphorus (P), Magnesium (Mg), Nitrogen (N), pH, and Potassium (K). Temperature measurements were made on the spot every 15 days. At the end of the experiment, all treatments reached the standards of humidity, temperature, pH, and NPK, established in Normative Instruction No. 25/200 for organic fertilizers, from the Ministry of Agriculture and Livestock of Brazil. Thus, the results demonstrated the efficiency of the mechanized composting process for the treatment of bovine, swine, and poultry manure, producing a high-quality organic compost.